Investigating factors and stimuli affecting the empowerment of rural women (Case study: Zanjan city) - zahra tarasi; hosin Karimzadeh; mohsen Aghayari hir (تحقیقات کاربردی علوم جغرافیایی)
While women account for about half the population of rural areas, they have always been considered as vulnerable populations of the community. Considering empowerment and its effective factors can increase their participation in livelihoods and increase their ability to help increase their family income. Therefore, the aim of this study was to investigate the factors and drivers that affect the empowerment of rural women. The present research is a descriptive-analytical one. The data gathering tool was a questionnaire and interviewed with rural women in Zanjan. The statistical population includes rural women in Zanjan city (N = 43559). Using Cochran's formula and quotient sampling, 381 women over 20 years old were selected as samples. Data were analyzed using one-sample t-test and binary logistic regression tests. The results showed that among the 29 variables in the study, 14 variables significantly had a significant relationship with the empowerment of rural women in Zanjan. Accordingly, economic factors (0.1171), psychological (0.197) and personal factors (109.10) had the most effects on empowerment of rural women (dependent variable). The results of this study can be used to identify the factors affecting the empowerment of rural women and removing the barriers related to it in the villages of the region and in general in the villages of the country.